Influence of 5G Technology on Educational Telecommunications and Networking - Umar Ibrahim; Umar Isah; Jamilu Ibrahim Argungu; Bashar Shuaibu (MultiTech Publisher, 2023)
The rapid proliferation of 5G technology has ushered in a new era of connectivity, offering unprecedented speed and reliability. This study explores the profound impact of 5G technology on educational telecommunications and networking, shedding light on its transformative potential within the realm of education. Through an in-depth analysis of current literature, case studies, and emerging trends, we examine the ways in which 5G technology enhances educational experiences, empowers remote learning, and catalyzes innovative pedagogical approaches. Furthermore, we investigate the infrastructure and security considerations that support the successful integration of 5G within educational institutions, addressing both the promises and challenges. As the education landscape evolves in response to technological advancements, understanding the multifaceted influence of 5G technology is crucial for educators, policymakers, and stakeholders. This paper not only synthesizes existing knowledge but also provides valuable insights into the future of education in the 5G era.